Philtrum length and intercommissural distance in newborn infants. Issue 2 (April 1983) - Sivan, Y; Merlob, P; Reisner, S H
Abstract : In order to define standards for philtrum length and mouth width in the newborn infant, 198 term and preterm infants (27 to 41 gestational weeks) were examined. In every case the gestational age was determined chronologically and clinically and the philtrum length and mouth width (oral intercommissural distance) were measured by two observers using standard measurement techniques. Normal values are presented by plotting the mean +/- 2 SD for each gestational week versus the gestational age.